A journey through adolescents' food environments in Vietnam: Rural site insights (Moc Chau) - Nguyen, Hong Duong; Even, Brice; Nabuuma, Deborah; Thai, Hang Thi Minh (2025)
This site-specific video provides an overview of our research on adolescents' food environments in Vietnam, featuring participatory videos created by the adolescents themselves. It showcases selected excerpts that illustrate the diversity of food environments, available food options, and perspectives of adolescents in an urban, peri-urban, and rural setting. Full versions of the participatory videos are currently being used to support a community level co-design process aimed at improving adolescents' food environments.